Recovery of a Common Bean Landrace (Phaseolus vulgaris L.) for Commercial Purposes - Mallor, Cristina; Barberán, Miguel; Aibar, Joaquín (Frontiers in Plant Science, 2018)
The “Caparrona” bean is a landrace that was grown largely in Monzón, and for that reason, it is also known by the name of “Caparrona de Monzón.” Historical references mention that in the thirties of the last century, Caparrona beans reached a production higher than 200,000 kg. Nevertheless, the increasing modernization of agriculture at the end of the 20th century enhanced its replacement by newer varieties. As a result, only a few local growers continued producing Caparrona beans mainly for family use. However, in recent years, the high demand for local products, grown with environmentally friendly farming techniques, has reawakened interest in this local bean. In order to recover the Caparrona bean crop, a study was conducted with the aim of assessing this landrace, along with all the processes, from collecting seeds to securing the in situ and ex situ conservation. Six bean samples were initially collected from local farmers and the traditional knowledge was also recorded. After the first seed-borne virus test, two samples were rejected because of the positive results for Bean Common Mosaic Virus (BCMV). The four remaining samples were evaluated in a randomized complete block design with three replications at two locations. All through the growth phase of the plants, samples were taken for a virus test. Two samples tested positive for BCMV and were discarded. Between the two healthy seed samples, regarding morphology, chemical composition, and agronomic data, no significant statistical differences were found. Therefore, both samples were selected for commercial production. The seeds obtained from the assays were transferred to a recently created producers’ association, which registered a private label to commercialize the Caparrona beans as a gourmet product. Seeds are also available from the Spanish BGHZ-CITA public genebank.